2022
DOI: 10.3389/pore.2022.1610096
|View full text |Cite
|
Sign up to set email alerts
|

Co-Detection of VEGF-A and Its Regulator, microRNA-181a, May Indicate Central Nervous System Involvement in Pediatric Leukemia

Abstract: Central nervous system (CNS) involvement is a leading cause of therapy-refractory pediatric acute lymphoblastic leukemia (pALL), which is aggravated by underdiagnosing CNS disease with the currently used cell-based approach of cerebrospinal fluid (CSF) diagnostics. Our study focused on developing novel subcellular CNS leukemia indicators in the CSF and the bone marrow (BM) of patients with pALL. Serial liquid biopsy samples (n = 65) were analyzed by Elisas to measure the level of essential proteins associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Evidence from ALL trials with hematopoietic growth factors is mixed; some studies suggest a reduction in severe infections by myeloid growth factors, whereas others report no effect [ 71 ]. Growth factors, like VEGF-A, have also been tied to CNS invasion in pediatric leukemia [ 72 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence from ALL trials with hematopoietic growth factors is mixed; some studies suggest a reduction in severe infections by myeloid growth factors, whereas others report no effect [ 71 ]. Growth factors, like VEGF-A, have also been tied to CNS invasion in pediatric leukemia [ 72 ].…”
Section: Resultsmentioning
confidence: 99%
“…Central nervous system infiltration has long been considered an important factor in describing potential pediatric leukemia prognoses. Recent work found that the co-detection of the growth factor VEGF-A and microRNA-181a may indicate central nervous system involvement in pediatric leukemia [ 72 ]. Finally, there is a plethora of evidence that shows older age, namely >10 years of age at diagnosis, to be associated with more negative outcomes in pediatric acute leukemias [ 77 ].…”
Section: Resultsmentioning
confidence: 99%
“…For this reason, inhibition of miR-181a-5p can be used as a therapeutic strategy for the treatment of ALL [ 67 ]. Moreover, in research by Egyed B et al carried out on various ALL genetic subgroups as normal karyotype, hyperdiploid, high hyperdiploid, KMT2A-rearranged, P2RY8-CRLF2 translocated, CDKN2A deleted and ETV6 deleted, the level of miR-181a or miR-181a in combination with Vascular endothelial growth factor A (VEGF-A) detected in the cerebrospinal fluid can be useful in the future as a marker of central nervous system (CNS) involvement in pediatric ALL [ 68 , 69 ]. A study by El-Khazragy N et al found that a high level of miR-181a and miR-155 in bone marrow cells was correlated with a higher risk of recurrence and poor response to treatment.…”
Section: Mirna In Pediatric Allmentioning
confidence: 99%